Sistem Penunjang Keputusan dalam Penentuan Calon Kepala Madrasah dengan Metode Weighted Product - Silvia, Ade; Sumijan, S (Jurnal Informasi dan Teknologi, 2021)
Madrasah is one of educational institutions integrated in the system of national education as outlined in UU Sisdiknas No. 2 Tahun 1989 and updated in the UU No. 2 Tahun 2003. The manager or the headmaster of madrasah plays the most significant role in the progress of madrasah, having a variety of functions such as managerial and supervisional ones with implication on its physical and non physical aspects. Therefore, it is very essential to choose a headmaster of certain madrasah out of the best possible candidate. In West Sumatera, election of headmaster through promotion and rotation lies upon the authortity of the provincial office of the Ministry of Religious Affairs, i.e. its Head of Office and selection committee. To this time, the basis for the election depends on simple observation, interviews and a kind of selection process for a number of teachers sent by the regency offices of the Ministry of Religious Affairs. This survey is conducted to rank all promoted candidates according to certain criteria outlined by the regulations by computerised information system. The method used in this survey is weighted product, one of the methods of the Decision Support System DSS. With this method in the system, all possible candidates will be ranked and the selection commitee will need less time and more accuration to pick the best ones. It is hoped that this product will be a contribution to be used by the provincial office of the Ministry of Religious Affairs in West Sumatra and can be adjusted to needs of the office.